2017
DOI: 10.1002/cjce.22995
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional effect of graphite flow field channels of a direct methanol fuel cell under different operating conditions

Abstract: Direct methanol fuel cells are a potential candidate to replace traditional power sources for portable applications. The flow field design, manufacture, and optimization are of great significance to the cell performance. When the scale of flow channels decreases to the level of submillimeter‐scale, it is favourable to the reactant and product management. This paper focuses on the effectiveness of using a multi‐tooth planing technique to create submillimeter‐scale parallel channels in a graphite sheet. Besides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…It is worth to mention that, particularly when dealing with samples upscale, the flow pattern of reactant distributors is of utter importance in determining local performance distribution; indeed, numerous works are present in the literature focusing on the identification of optimal distributor geometries [22][23][24][25][26][27][28]. In this work, instead, we intend to demonstrate that an alternative, or additional, approach can pursue local performance homogenization and stability improvement by optimizing local properties of the MEA given a specific a flow pattern for the distributors.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth to mention that, particularly when dealing with samples upscale, the flow pattern of reactant distributors is of utter importance in determining local performance distribution; indeed, numerous works are present in the literature focusing on the identification of optimal distributor geometries [22][23][24][25][26][27][28]. In this work, instead, we intend to demonstrate that an alternative, or additional, approach can pursue local performance homogenization and stability improvement by optimizing local properties of the MEA given a specific a flow pattern for the distributors.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that a metal mesh achieves a better performance at a low methanol concentration. Tan et al 26 studied the effects of the flow channel length on the performance of a DMFC, and concluded that using small channels of sub-millimeter dimensions is preferable, particularly at the anode side. They also found an increase in the parasitic pumping loads through the use of narrower channels.…”
Section: Introductionmentioning
confidence: 99%